Detection of Microvesicle miRNA Expression in ALL Subtypes and Analysis of Their Functional Roles - 李雯英 陈小梅 熊薇 郭冬梅 卢力 李慧玉 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Microvesicles （MVs） are the heterogeneous mixtures of vesicles. MVs released by leukemia cells constitute an important part of the leukemia microenvironment. MVs might act as important reser- voirs of microRNAs （miRNAs）. It is worth evaluating whether MVs possess some unique miRNA con- tents that are valuable in understanding the pathogenesis. In this study, we investigated the miRNA ex- pression patterns of Nalm-6-derived MVs, Jurkat-derived MVs and normal cell-derived MVs using miRNA microarrays. The potential target genes regulated by differentially expressed miRNAs were also predicted and analyzed. Results demonstrated that 182 miRNAs and 166 miRNAs were differentially expressed in Nalm-6-MVs and Jurkat-MVs, respectively. Many oncogenes, tumor suppressors and sig- nal pathway genes were targeted by these aberrantly expressed miRNAs, which might contribute to the development of B-ALL or T-ALL. Our findings expanded the potential diagnostic markers of ALL and provided useful information for ALL pathogenesis.